Livestock populations in Kenyan rangelands: An analysis of trends using census and aerial survey data - Leeuw, P.N. de (Research Inst. for Animal Husbandry, 1990)
Presents a comparative evaluation of population estimates based on data from ground and aerial surveys for a number of districts for which contemporary records are available. Gives an exploratory analysis of aerial surveys in six northern districts to detect trends in livestock populations over time. Includes a detailed analysis of ground and aerial survey data for Kajiado District.